INVESTORS' TRUST AND RISK PERCEPTION USING THE INVESTMENT PLATFORM: A GENDER PERSPECTIVE - Annisa Hakim Zamzami (Dinasti International Journal of Education Management And Social Science, 2021)
The development of the technology in financial sector has become opportunities for online trading platform developers, especially in investment. This is a form of encouragement from manual transactions transformation towards digital. The Financial Services Authority stated that of many websites and online investment platforms did not get permission from the them. This will has impacts on the risks that will be carried by the people who use it. On the other hand, as the development of online investment platforms grows because of COVID, the impact is that more people carry out online investment transactions to earn profits that is now mainly dominated by male society. Many perspectives associating the gender gap, such as the risky decision-making level and the perspective of women's trust level in using low investment platforms. Therefore, this study aims to test out perceived trust and risk of using online investment platforms from gender perspective. Thus, this research can be a review from educational institutions or the investor community in Indonesia to encourage women's participation in improving the economy in Indonesia through trading. This research uses clause method by looking at the causality of independent and dependent variable. The data collection technique uses survey by sending google form links to investors' communities on social media. The results of the survey were checked for reliability and validity prior to multigroup analysis using SmartPLS. The results showed that gender was not able to moderate the effect of perceived trust and perceived risk on the intention to use online investment platforms.